Response of Quality and Yield of Foxtail Millet to Nitrogen and Zinc Application - Genlan Han; Jiang Wang; Haiyan Zhao; Dan Wang; Yanyan Duan; Ruihua Han; Meng’en Nie; Lijie Zhao; Huiling Du (Agriculture, 2023)
The effect of nitrogen and zinc treatment on quality and yield was studied to provide a theoretical basis for generating high-quality and high-yielding foxtail millet. In the years 2021–2022, ‘Jingu 21’ was utilized as the test material in a split-plot design. The main plot was subjected to nitrogen treatment, while the sub-plot was treated with zinc. An arrangement of random blocks was employed. Four levels of nitrogen application (0 kg/hm2, 120 kg/hm2, 180 kg/hm2, 240 kg/hm2) and three levels of zinc application (20 mg/L, 40 mg/L, 80 mg/L foliar spraying) were set, resulting in a total of twelve treatments. Each treatment was replicated three times, with each plot covering an area of 15 m2. (1) The findings indicated that the contents of crude fat and crude protein in foxtail millet increased initially and then decreased with the increase in nitrogen application concentration. Additionally, the protein components were found to be in the following order: gliadin > albumin > glutenin > globulin. (2) Adding an appropriate amount of nitrogen fertilizer under the same zinc level promoted the contents of amylose, total carotenoids, and flavonoids in millet to some extent. Over the course of two years, the content of flavonoids in millet was highest when treated with N180Zn40 (nitrogen 180 kg/hm2, zinc 40 mg/L), showing an increase of 50.14% and 58.67%, respectively, compared to the treatment of applying zinc fertilizer alone at the same zinc level. (3) The phytic acid content and phytic acid/zinc molar ratio exhibited a pattern of initially decreasing and then increasing with the rise in nitrogen and zinc concentrations. (4) The application of zinc fertilizer and increased nitrogen fertilizer for two consecutive years had a significant impact on the yield of millet. Additionally, the application of zinc fertilizer had a highly significant effect on both the ear weights and thousand-kernel weights of millet (p < 0.001). The results demonstrated a positive synergistic effect when nitrogen fertilizer and zinc fertilizer were applied together. This combination significantly improved millet yield and thousand-kernel weights, enhanced the nutritional quality, and increased the content of functional components. Additionally, it also improved the availability of zinc.